Philosophical-theological and educational considerations of the “Gender Ideology” - Gutierrez, Flavio (2017)
Given the alarm the presence in the educational curriculum of the so-called "Gender Ideology" has generated among of a large number of Peruvian parents, the author analyzes the subject from different perspectives. First, from a philosophical perspective, based on the humanistic existentialism of Simon de Beauvoir and in Marxist ideology. Second, from a theological perspective, emphasizing that this ideology contradicts the biblical-theological view that man was created in the image and likeness of God and that it constitutes a deconstruction of the fundamental cell of society, i.e., the family. Last, from an educational perspective, as such ideology would imply that gender is the result of culture alone and not human nature. Against "Gender Ideology", the author highlights the Christian-humanist vision of man that conceives it as a bio-psycho-social unit, speaking of the dimensions of man.